When women rule the court : gender, race, and Japanese American basketball - Willms, Nicole; Project Muse. (New Brunswick : Rutgers University Press, 2017)
"For nearly one hundred years, basketball has been an important part of Japanese American life. Women's basketball holds a special place in the contemporary scene of highly organized and expansive Japanese American leagues in California, in part because these leagues have produced numerous talented female players. Using data from interviews and observations, Nicole Willms explores the interplay of social forces and community dynamics that have shaped this unique context of female athletic empowerment. As Japanese American women have excelled in mainstream basketball, they have emerged as local stars who have passed on the torch by becoming role models and building networks for others"--
Chapter 6. Conclusion. "It's a Testament of What the Japanese Leagues Can Do for Young Girls"Acknowledgments; Methodological Appendix; Notes; Bibliography; Index; About the Author
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Japanese Americans -- Recreation -- California; Japanese Americans -- California -- Social life and customs; Japanese American basketball players -- California -- History; Women basketball players -- California; Basketball for women -- California -- History; Américains d'origine japonaise -- Loisirs -- Californie; Américains d'origine japonaise -- Californie -- Mœurs et coutumes; Joueuses de basket-ball -- Californie; Basket-ball féminin -- Californie -- Histoire; SOCIAL SCIENCE / Women's Studies; SOCIAL SCIENCE / Ethnic Studies / Asian American Studies; SPORTS & RECREATION / Basketball; GAMES / Gambling / Sports; SPORTS & RECREATION / Business Aspects; SPORTS & RECREATION / Essays; SPORTS & RECREATION / History; SPORTS & RECREATION / Reference; TRAVEL / Special Interest / Sports; Basketball for women; Japanese American basketball players; Japanese Americans -- Social life and customs; Women basketball players; California; japan, japanese, japanese american, basketball, american basketball, japanese basketball, female athlete, women's basketball, court, point guard, shooting guard, center, whistle, sports, women in sports; History